Ta'lim Al-balaghoh Fi Dhou'i Nadzriyah An-nadzom ;inda Abdi Al-Qohir Al-Jurjani W a Atsaruhu Fi Al-Qudrph 'Ala At-tadzawwuq Al-balaghy Lada Tholibat Ma'hadi Daari Arrhman Li At-tarbiyah Al-Islamiyah Depok: تعليم البلاغة في ضوء نظرية النظم عند عبد القاهر الجرجاني وأثره في القدرة على التذوق البلاغي لدى طالبات معهد دار الرحمن للتربية الاسلامية ديفوك - Tsuaibatul Islamiyah; Zainal Muttaqin; Raswan Raswan; Ahmad Dardiri (Al-TARQIYAH: Jurnal Pendidikan Bahasa Arab, 2023)
Because of the Students are need the appreciate rhetoric to appreciate Arabic literary texts so that they feel proud of their language and their heritage, and because of the teachers who teach balaghoh in the seccond class off high school in the islamic boarding school only teached balaghoh by using the book that was used as reference in Islamic boarding schools by explaining it and memorizing it so that students feel bored and this causes weaknesses in their rhetoric abilities. The results of this study are that the way of learning balaghoh with the Nadzam Shaykh Abdul Qohir Al-Jurjani Theory is by following the steps: Introduction, Explanation, Application of Shaykh Abdul Qohir's symbols which are separated from the textual context to perfect its unity and structure, then Analyze it by explaining the elements of the nahwu, training students to understand the differences in the symbols of the nahwu and explaining the differences and the reasons assisted by the shaykh's theory and then practicing. And the effect of applying nadzam theory in Balaghah learning is that there are more than 50% of students who produce high scores in written test results about analyzing texts using nadzam theory. This shows that this theory helps students to have the ability to comprehend balaghoh because someone who having an appreciation of balaghoh with his intelligence will be able to explain the advantages contained in the text.